SOIL EVOLUTION AFTER FIRE IN QUERCUS-ILEX AND PINUS-HALEPENSIS FORESTS - FERRAN, A.; SERRASOLSAS, I.; Vallejo, V. R. (RESPONSES OF FOREST ECOSYSTEMS TO ENVIRONMENTAL CHANGES, 1992)
Four contrasted burned sites in Catalonia (NE Spain) have been compared to-illustrate the diversified response to fire depending on the interaction of substrate-vegetation characteristics. Data from plant cover evolution, forest floor layers and soil chemical properties demonstrated that the garrigue on limestone is the most resilient ecosystem as a result of the resprouting capacity of Ouercus coccifera and the high soil stability. The shrubland on marls was however, the least resilient, with the poorest plant regeneration and greatest erosion rates. The plant communities on conglomerates and the holm oak forest on schists, represented intermediate situations, where the variable degree of erosion and nutrient losses were compensated by a rapid plant colonization just after the fire.
The following values have no corresponding Zotero field: periodical: RESPONSES OF FOREST ECOSYSTEMS TO ENVIRONMENTAL CHANGES pub-location: BARKING ESSEX
Keywords: burned sites; ecosystem resilience; fire; Quercus coccifera; Quercus ilex; Shrubland; Spain